Sedimentary processes for the geosynthesis of heterocyclic aromatic hydrocarbons and fluorenes by surface reactions - Asif, Muhammad; Alexander, Robert; Fazeelat, T.; Grice, Kliti (Elsevier Science, 2010)
Laboratory experiments have shown that activated carbon catalyses the reactions of biphenyls (BPs) with surface adsorbed reactants incorporating either S, O, N or methylene, leading to the formation of some common constituents reported in sedimentary organic matter (OM) namely, dibenzothiophene (DBT), dibenzofuran (DBF), carbazole (C) and fluorene (F). A relationship between the % abundance of the hetero element in the kerogen and the abundance of the related heterocyclic compound in the associated soluble OM supports the hypothesis that these reactions occur in Nature. More specific supporting evidence was obtained from the good relationship observed between methyl and dimethyl isomers of the reactant BPs and the methyl and dimethyl isomers of the proposed heterocyclic products.It is suggested that these aromatic compound distributions reported in sediments and crude oils from the Upper Indus Basin (Pakistan) and the Carnarvon Basin (NW Australia) are the result of a surface reactions of compounds with BP rings and surface adsorbed species of the hetero element on the surface of carbonaceous material